"Squeezing R&D": A Study of Organizational Slack and Knowledge Creation in NPD, Using the SECI Model1. Issue 6 (27th November 2013) - Richtnér, Anders; Åhlström, Pär; Goffin, Keith
<x xml:space="preserve">Abstract</x> During new product development (NPD), functional areas such as marketing, R&D, and manufacturing work together to understand customer needs, create product concepts, and solve technical issues. NPD is dependent on the creation of new knowledge and the interplay between tacit knowledge (knowledge that is difficult to articulate and codify) and explicit knowledge (knowledge that can be codified and documented). Knowledge creation requires time and resources, and the dichotomy facing senior management is how much spare capacity in NPD teams—so‐called organizational slack—is appropriate. Too much organizational slack and precious development resources will be wasted; but when slack is eliminated, there is a danger that knowledge creation will be severely hindered. There have been very few studies of organizational slack at the project level, and so the aim of our research was to examine the impact of changes in organizational slack on knowledge creation in NPD projects. Six projects were studied at two companies, over a two‐year period. Multiple sources of data were used to determine how changes in organizational slack impacted knowledge creation, which was operationalized using Nonaka's socialization, externalization, combination, and internalization (SECI) model. It was found that the creation of knowledge in NPD projects is susceptible to changes in organizational slack. A significant finding was that every time there were changes in organizational slack, there was always some impact on knowledge creation. Increased slack enabled knowledge creation; but, importantly, the impacts of decreasing organizational slack were often very negative and disrupted the work of NPD teams, particularly at the end of projects. Managers who feel that "squeezing R&D" is important should think again—their action might disrupt knowledge creation and compromise innovation.